ANALISIS KOMPARASI NILAI TUKAR PETANI TANAMAN PANGAN DENGAN NILAI TUKAR PETANI HORTIKULTURA DI SULAWESI TENGGARA - Sumono, Hadi; Iswandi, R Marsuki; Arif, La Ode Kasno; Zani, Munirwan; Gafaruddin, Abdul; Dedu, La Ode Arfan (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The purpose of this study is to determine the development of the welfare of food crop farmers and the welfare of horticultural farmers, as well as to analyze the comparison of the welfare of food crop farmers and the welfare of horticultural farmers in Southeast Sulawesi Province. This study uses secondary data from the Central Statistics Agency in the form of exchange rate data for food crop farmers and exchange rates for horticultural crop farmers from January 2014 to December 2022, so that the number of observations is 108 months. Analysis of this research data using a paired t test. The results of this study show the welfare of farmers from 2014 to 2022 for fluctuating and unprosperous food crops. The exchange rate for horticultural farmers' welfare fluctuated and prospered from 2020 to 2022. The welfare of food crop farmers and the welfare of horticultural farmers are significantly different.